Multicultural Belief, Faith, and Behavior of District’s Aged Society to The Identity of Creative Recreation Area for A Cultural Tourism: A Case Study of Wutthakat Community, Jomthong Districts, Bangkok - Paengkasorn, Anucha; Thinthan, Sukanda; Tumkositi , Manintra; Houbcham , Busakorn (DEC Journal : Art and Design, 2024)
The Wutthakat community is located in the area of ​​an ancient temple, it has royal architecture in the reign of King Rama III and the community has a diverse heritage of wisdom in the community. The research project was performed out using a mixed methods research design. A group of local elders was interviewed for qualitative study. Local artists, creatives, agency representatives, academics, and specialists to be evaluated, synthesized, and combined with theories to design a creative recreation area for cultural tourism. The study indicated that 1) Wutthakat community context Famous tourist destinations, Thai-Chinese cultural resources influenced by King Rama III, and intellectual heritage like the Pi-phat Kru Thongkham group are its strengths, Cockatoo-tiger stabbing game, etc. 2) Wutthakat seniors live simply, be self-sufficient and happy with your home and enjoy group fun and relaxing activities. 3) The possibility of local expenses to develop an identity that matches community elderly behavior and encourage beautiful creation Preservation and emphasis on the area's original attractiveness are its goals. Based on study results Researchers advise using research results and future research. Local leaders and residents It increase involvement and comprehension. Designing a creative cultural tourism leisure area. In order to enhance the overall well-being of the elderly population and foster the establishment of a secure community. The individual expresses a willingness to engage in sustainable adaptation. The study indicated that 1) Wutthakat community context Famous tourist destinations, Thai-Chinese cultural resources influenced by King Rama III, and intellectual heritage like the Piphat Kru Thongkham group are its strengths. Cockatoo-tiger stabbing game, etc. 2) Wutthakat seniors live simply. Be self-sufficient and happy with your home. and enjoy group fun and relaxing activities. 3) The possibility of local expenses to develop an identity that matches community elderly behavior. and encourage beautiful creation Preservation and emphasis on the area's original attractiveness are its goals. Based on study results Researchers advise using research results and future research. Local leaders and residents It increase involvement and comprehension. Designing a creative cultural tourism leisure area. In order to enhance the overall well-being of the elderly population and foster the establishment of a secure community. The individual expresses a willingness to engage in sustainable adaptation. Key word: Multiculture, Aged Society, The Identity, Creative Recreation Area, Cultural Tourism